Factors Causing Students’ Lack of Confidence in Answering Recount Text Questions in English Language Learning - Maulidah, Rizqiyatul; Muhtarom; Datik, Aisyiyah Munawar (ICONELT, 2024)
The purpose of this study is to determine the contributing elements to students’ insecurity when responding to recount text questions during classroom instruction in the English language. This study, which included 31 Grade 8 students from SMPN 2 Gresik, used a quantitative methodology and a descriptive design. A survey was used to gather data, and the questionnaire covered both external and internal elements, such as peer pressure and instructional methods, as well as internal factors, like English proficiency and self-concept. The aim revealed that vocabulary comprehension difficulties (51.6%) and boring teaching techniques (67.1%) were the most significant factors influencing students’ self-confidence. According to this study, it is critical to boost students’ confidence and enhance their English language learning outcomes to create more engaging teaching strategies and provide extra assistance for those who need it.